2022
DOI: 10.1155/2022/3769965
|View full text |Cite|
|
Sign up to set email alerts
|

IoT-Based Water Quality Assessment System for Industrial Waste WaterHealthcare Perspective

Abstract: The environment, especially water, gets polluted due to industrialization and urbanization. Pollution due to industrialization and urbanization has harmful effects on both the environment and the lives on Earth. This polluted water can cause food poisoning, diarrhea, short-term gastrointestinal problems, respiratory diseases, skin problems, and other serious health complications. In a developing country like Bangladesh, where ready-made garments sector is one of the major sources of the total Gross Domestic Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Decentralized SWQMS offers cost reduction, permits precise matching of increasing wastewater capacity needs, takes advantage of the homogeneousness of wastewater streams, and does not require large sewer systems for distributing treated water. In addition, the failure probability is lower than that of centralized systems [59].…”
Section: Iotmentioning
confidence: 95%
“…Decentralized SWQMS offers cost reduction, permits precise matching of increasing wastewater capacity needs, takes advantage of the homogeneousness of wastewater streams, and does not require large sewer systems for distributing treated water. In addition, the failure probability is lower than that of centralized systems [59].…”
Section: Iotmentioning
confidence: 95%
“…The use of information and communication technology (ICT) applications, including the Internet of Things (IoT), has impacted many fields. One of the applications is water quality monitoring (Dhruba et al, 2022;Jan et al, 2021;Lakshmikantha et al, 2021;Moparthi et al, 2018). It is important to maintain the quality of water in shrimp ponds as shrimp development is very sensitive to water conditions in the ponds.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%